Detection of Bcl-2 gene in leukaemic rats using an EvaGreen real-time RT-PCT assay - Haron, Nursyuhada; Hamzah, Hazilawati; Al-Salih, Hutheyfa A. H.; Shaari, Mohd Rosly; Sithambaram, Shanmugavelu; Mohamed Mustapha, Noordin; Sabri, Jasni (Universiti Putra Malaysia Press, 2011)
Bcl-2 is an anti-apoptotic gene that is involved in the apoptosis process. Suppression of apoptosis by anti- apoptotic gene can contribute to the occurrence of diseases such as leukaemia. The objectives of this study were 2-folds: first, to compare the sensitivity of an EvaGreen quantitative real-time reverse transcriptase polymerase chain reaction (qRT-PCR) with a conventional RT-PCR for the amplification of the Bcl-2 gene; second, to determine the expression of the Bcl-2 gene in N-methyl-N-nitrosourea (MNU)-induced leukaemiain rats using the EvaGreen qRT-PCR assay. A total of 32 male Sprague Dawley rats were assigned into two groups (n=16), namely, control and MNU groups. In particular, MNU was administered intraperitoneally (i.p) at a dose of 60 mg/kg body weight per injection at two times per week for 2 consecutive weeks. The rats were sacrificed after five months and blood samples were collected for RNA extraction and haemogram. The RNAs were converted into cDNA and amplified using both the EvaGreen qPCR and the conventional PCR assays. All the results were normalised with a housekeeper gene, i.e. glyceraldehyde 3-phosphate dehydrogenase (GADPH). The products of amplification were run on gel electrophoresis and all the results were then compared. Based on the relative intensity of the bands, the EvaGreen qRT-PCR assay was highly sensitive compared to the conventional RT-PCR assay as the Bcl-2 gene could not be amplified using the conventional RT-PCR. Interestingly, the results in this study showed that the expression of Bcl-2 was higher in rats with marked lymphocytosis as compared to the leukaemic rats with normal to mildly increase in lymphocyte count. In conclusion, EvaGreen qRT-PCR assay is more sensitive compared to the conventional RT-PCR, and Bcl-2 gene is abundantly expressed in leukaemic rats with marked lymphocytosis compared to the leukaemic rats with normal to mildly increase in lymphocyte number.